2022
DOI: 10.55493/5002.v12i5.4490
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Corporate Governance Mechanisms on Earnings Management in Malaysian Manufacturing Companies

Abstract: Earnings management (EM) firms produce less predictable accounting earnings that do not reflect the company's genuine financial success. However, EM is regarded as one of the most significant issues regarding financial reporting, especially in light of the COVID-19 pandemic. Nevertheless, this paper aims to investigate the effect of corporate governance mechanisms on earnings management in Malaysian manufacturing companies (MMCs). Data was collected from 2010 to 2019 for MMCs. By highlighting the updating of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Gruchmann et al (2020) found that digital business models and digitalization intersect to reshape business models within the sea freight industry which affects the potential for enhanced operational efficiency and effectiveness. The continuous digital revolution is playing a key role in determining economic growth, business strategies, and sustainability (Al-Zaqeba et al, 2022;Alflaieh, 2022). The many facets of digitalization's impact have been studied by academics, with an emphasis on sustainability, taxes, environmental legislation, and how they affect business performance and social well-being.…”
Section: Digital Taxation On Customs Efficiency and Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Gruchmann et al (2020) found that digital business models and digitalization intersect to reshape business models within the sea freight industry which affects the potential for enhanced operational efficiency and effectiveness. The continuous digital revolution is playing a key role in determining economic growth, business strategies, and sustainability (Al-Zaqeba et al, 2022;Alflaieh, 2022). The many facets of digitalization's impact have been studied by academics, with an emphasis on sustainability, taxes, environmental legislation, and how they affect business performance and social well-being.…”
Section: Digital Taxation On Customs Efficiency and Sustainabilitymentioning
confidence: 99%
“…The advent of digital technologies has transformed traditional customs operations, enabling streamlined processes and enhanced accuracy (Raza et al, 2023). In this literature review, this paper explores the effect of digital taxation and digital accounting on customs efficiency and corporate sustainability at customs ports, focusing on key factors such as Customs Regulations Compliance (CRC), Customs Port Efficiency (CPE), Customs Data Integration (CDI), Cross-Border Trade Facilitation (CBTF), Compliance Technology Adoption (CTA), Customs Audit Trail Transparency (CATT), Customs Reporting Accuracy (CRA), and Customs Process Automation (CPA) (Al-Zaqeba et al, 2022;Abdul Aleem, 2022). However, the legal and regulatory frameworks governing cross-border business to be adhered to, customs regulations must be complied with.…”
Section: Globalization Of Trade and Commercementioning
confidence: 99%
“…The Human Resources Department has chosen two human resource management strategies that can help organizations by enhancing organizational effectiveness and meeting individual requirements. Al-Zaqeba et al (2022) explained that instead of viewing the needs of the organization and the needs of individuals as two separate opposites and that achieving either of them will be at the expense of the other, behavioral research showed the need to treat individuals as resources rather than as people. Take into consideration the approach to human resources that both the goals of the organization and the needs of individuals complement each other rather than being at the expense of each other.…”
Section: Human Resource Management Practicesmentioning
confidence: 99%
“…Islamic businesses and organizations are now concentrating on their Corporate Social Responsibility (CSR) programs and broadening them through smart zakat distribution. However, as a result of shifting cultural norms and expectations, businesses are feeling pressure from the public to increase their openness and accountability for social responsibility (Al-Zaqeba, Abdul Hamid, Ineizeh, Hussein, & Albawwat, 2022 ). Indeed, as stated in the Qur'an and the Prophet Muhammad's (P.B.U.H.)…”
Section: Introductionmentioning
confidence: 99%